2020
DOI: 10.21203/rs.3.rs-51729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long Non-coding RNA PTPRG-AS1 Promotes Cell Tumorigenicity in Epithelial Ovarian Cancer by Decoying microRNA-545-3p and Consequently Enhancing HDAC4 Expression

Abstract: Background: Long non-coding RNA PTPRG antisense RNA 1 (PTPRG-AS1) deregulation has been reported in various human malignancies and identified as an important modulator of cancer development. Few reports have focused on the detailed role of PTPRG-AS1 in epithelial ovarian cancer (EOC) and its underlying mechanism. This study aimed to determine the physiological function of PTPRG-AS1 in EOC. A series of experiments were also done to identify the mechanisms through which PTPRG-AS1 exerts its function in EOC.Metho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, we revealed that lncRNA CASC9 regulates the progression of OSCC cells by sponging miR-545-3p to upregulate LAMC2, a mechanism different from that reported by Yang et al Therefore, the regulatory mechanism of lncRNA CASC9 in OSCC has expanded. miR-545-3p, a member of the miRNA family, has been proven to be a tumor suppressor in multiple cancers, such as lung cancer and ovarian cancer [21,23]. Specifically, in a previous report, miR-545-3p sponged by lncRNA PTPRG-AS1 to target histone deacetylase 4 suppressed cell migration and invasion in epithelial ovarian cancer [23].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, we revealed that lncRNA CASC9 regulates the progression of OSCC cells by sponging miR-545-3p to upregulate LAMC2, a mechanism different from that reported by Yang et al Therefore, the regulatory mechanism of lncRNA CASC9 in OSCC has expanded. miR-545-3p, a member of the miRNA family, has been proven to be a tumor suppressor in multiple cancers, such as lung cancer and ovarian cancer [21,23]. Specifically, in a previous report, miR-545-3p sponged by lncRNA PTPRG-AS1 to target histone deacetylase 4 suppressed cell migration and invasion in epithelial ovarian cancer [23].…”
Section: Discussionmentioning
confidence: 95%
“…miR-545-3p, a member of the miRNA family, has been proven to be a tumor suppressor in multiple cancers, such as lung cancer and ovarian cancer [21,23]. Specifically, in a previous report, miR-545-3p sponged by lncRNA PTPRG-AS1 to target histone deacetylase 4 suppressed cell migration and invasion in epithelial ovarian cancer [23]. However, the function of miR-545-3p in OSCC has not yet been investigated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MiR-545-3p dysregulation has been reported in diverse cancers. Shi et al reported that miR-545-3p was downregulated in epithelial ovarian cancer (35); Hao et al showed that miR-545-3p inhibits the proliferation and differentiation of osteoblasts (36); and Zhong et al reported that miR-545-3p functions as a tumor suppressor in endometrial carcinoma (37). Furthermore, some studies indicate that miR-545-3p may be the target of circRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Significant evidence shows that abnormal regulation of miRNAs is related to the malignant progression of many cancers, and miRNAs are potential therapeutic targets for lung cancer [17]. For example, miR-545-3p has been studied in a variety of cancers including endometrial [18] and ovarian cancer [19]. Another study showed that miR-545-3p was expressed at low levels within NSCLC tumor and cultured cells [20].…”
Section: Introductionmentioning
confidence: 99%